2012
DOI: 10.1007/s11262-012-0850-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of KGH, the first human isolate of rabies virus in Korea

Abstract: The complete genome sequence of the KGH strain of the first human rabies virus, which was isolated from a skin biopsy of a patient with rabies, whose symptoms developed due to bites from a raccoon dog in 2001. The size of the KGH strain genome was determined to be 11,928 nucleotides (nt) with a leader sequence of 58 nt, nucleoprotein gene of 1,353 nt, phosphoprotein gene of 894 nt, matrix protein gene of 609 nt, glycoprotein gene of 1,575 nt, RNA-dependent RNA polymerase gene of 6,384 nt, and trailer region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Until recently, wild animals, such as raccoon dogs ( Nyctereutes procynoide koresis ) and badgers ( Meles meles ), have been the rabies reservoir in South Korea and especially raccoon dogs have played a key role in transmitting rabies since 1993. Thus, raccoon dogs have become the main target animal for controlling rabies [ 1 2 3 ]. As the disease spread into southern regions of Gyeonggi province in 2013, the Korean Veterinary Authority strengthened preventative measures against raccoon dogs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, wild animals, such as raccoon dogs ( Nyctereutes procynoide koresis ) and badgers ( Meles meles ), have been the rabies reservoir in South Korea and especially raccoon dogs have played a key role in transmitting rabies since 1993. Thus, raccoon dogs have become the main target animal for controlling rabies [ 1 2 3 ]. As the disease spread into southern regions of Gyeonggi province in 2013, the Korean Veterinary Authority strengthened preventative measures against raccoon dogs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, poor laboratory-based surveillance in the mountainous areas of the DMZ limited case detection among wildlife, after the control of canine rabies by 1985. Recognizing these limitations, public health, wildlife health and veterinary programs were augmented in a One Health context (Yang et al 2011b;Park et al 2013;Oem et al 2013;Cheong et al 2014). Following dog rabies control, improved laboratory-based surveillance and viral characterization of cases showed raccoon dogs as important in RABV transmission (Oem et al 2014).…”
Section: Asiamentioning
confidence: 99%
“…In comparison to the other 40 RABV strains whose complete genomes have been sequenced, there is one unique amino acid replacement in the KGH strain in a region of the phosphoprotein (P protein), which is related to STAT1 control. Phylogenetic analysis showed that KGH is most closely related to the NNV-RAB-H strain isolated in India and the transplant RABV serotype 1 strain [ 4 ].…”
Section: Introductionmentioning
confidence: 99%